Improving the muon track reconstruction of IceCube and IceCube-Gen2 - Bradascio, Federica; Glüsenkamp, Thorsten (EPJ Web of Conferences, 2019)
IceCube is a cubic-kilometer Cherenkov telescope operating at the South Pole. Its goal is to detect astrophysical neutrinos and identify their sources. High-energy muon neutrinos are identified through the secondary muons produced via charge current interactions with the ice. The present bestperforming directional reconstruction of the muon track is a maximum likelihood method which uses the arrival time distribution of Cherenkov photons registered by the experiment’s photomultipliers. Known systematic shortcomings of this method are to assume continuous energy loss along the muon track, and to neglect photomultiplier-related effects such as prepulses and afterpulses. This work discusses an improvement of about 20% to the muon angular resolution of IceCube and its planned extension, IceCube-Gen2. In the reconstruction scheme presented here, the expected arrival time distribution is now parametrized by a predetermined stochastic muon energy loss pattern. The inclusion of pre- and afterpulses modelling in the PDF has also been studied, but no noticeable improvement was found, in particular in comparison to the modification of the energy loss profile.